2021
DOI: 10.1016/j.neubiorev.2020.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Autism spectrum disorder and pupillometry: A systematic review and meta-analysis

Abstract: Pupillometry, measuring pupil size and reactivity, has been proposed as a measure of autonomic nervous system functioning, the latter which might be altered in individuals with autism spectrum disorder (ASD). This study aims to evaluate if pupillary responses differ in individuals with and without ASD. After performing a systematic literature search, we conducted a meta-analysis and constructed a qualitative synthesis. The meta-analysis shows a longer latency of the pupil response in the ASD-group as a substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
49
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 96 publications
(190 reference statements)
2
49
2
Order By: Relevance
“…Years later, the same authors [ 23 ], using the same methodology, included a baseline measure, and observed that the group of children with ASD showed greater pupil dilation at that moment in comparison to the neurotypical group. These results are in line with the theory of the existence of a high level of arousal in children with ASD [ 11 ] and it has been speculated that acetylcholine, a neurotransmitter in the ANS, is dysregulated in people with ASD [ 24 ]. In this same direction, Martineau et al [ 25 ] observed different behaviour patterns in a group of children with ASD compared to neurotypical children on visualising slides of faces, avatars and objects.…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…Years later, the same authors [ 23 ], using the same methodology, included a baseline measure, and observed that the group of children with ASD showed greater pupil dilation at that moment in comparison to the neurotypical group. These results are in line with the theory of the existence of a high level of arousal in children with ASD [ 11 ] and it has been speculated that acetylcholine, a neurotransmitter in the ANS, is dysregulated in people with ASD [ 24 ]. In this same direction, Martineau et al [ 25 ] observed different behaviour patterns in a group of children with ASD compared to neurotypical children on visualising slides of faces, avatars and objects.…”
Section: Introductionsupporting
confidence: 88%
“…Recent research has suggested that eye movements and the reactions to verbal/visual stimuli used in eye-tracking methodology could be used as signs or biomarkers of early diagnosis of ASD [ 9 , 10 , 11 ]. Eye-tracking is a non-invasive and relatively economical methodology that might potentially be used to detect early biomarkers of autism in children of very early ages (even less than 12 months) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two measurable components of the PLR can be linked to distinct mechanisms. PLR latency (constriction onset time) is likely regulated by neural signal transduction efficiency (Dinalankara, Miles, Takahashi, & Yao, 2017), whereas PLR amplitude is highly, but not exclusively, dependent on cholinergic and norepinephrine neurotransmission efficiency (Heller, Perry, Jewett, & Levine, 1990;Loewenfeld, 1999;Lynch, 2018;de Vries, Fouquaet, Boets, Naulaers, & Steyaert, 2021) neural processes implicated in early ASD (Abreu-Villac ßa, Filgueiras, & Manhães, 2011;Ben-Bashat et al, 2007). Indeed, preliminary evidence indicates altered PLR during infancy associates with later ASD, although results are mixed.…”
Section: Introductionmentioning
confidence: 99%
“…Investigating associations between developing candidate intermediate phenotypes like infant PLR and individual polygenic scores for ASD (PGS ASD )weighted sums of ASD-associated common genetic variants (Euesden, Lewis, & O'Reilly, 2015) could highlight developmental pathways through which common genetic liability manifests into later symptomology. To date, the relation between infant PLR and individual PGS ASD has not been investigated (de Vries et al, 2021).…”
Section: Introductionmentioning
confidence: 99%